Multi-layer titanium boride cladding Si3N4-based ceramic cutter and preparation method and application thereof

By combining the Si3N4 ceramic matrix with multi-layer titanium boride cladding to form a multi-layer titanium boride cladding Si3N4-based ceramic tool, the problems of insufficient toughness of titanium boride tool and serious wear in the prior art are solved, and cutting performance with high hardness, high toughness and high wear resistance are achieved.

CN119751085APending Publication Date: 2025-04-04GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411859180.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing titanium boronide ceramic tools are not tough enough during the high-speed cutting of titanium alloys and are prone to cracking. However, Si3N4 ceramic tools are seriously worn during cutting and have low anti-cracking ability.

Method used

The multi-layer titanium boride clad Si3N4-based ceramic tool is used to improve the hardness, toughness and wear resistance of the tool by combining the Si3N4 ceramic matrix with the multi-layer titanium boride clad.

Benefits of technology

The tool is achieved with high hardness, high toughness and high wear resistance, significantly improving the cutting performance and life in titanium alloy cutting, and avoiding the phenomenon of cracking.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramics, and discloses a multilayer titanium boride cladding Si3N4-based ceramic cutting tool and a preparation method and application thereof.The multilayer titanium boride cladding Si3N4-based ceramic cutting tool is composed of a Si3N4 ceramic matrix and a multilayer titanium boride cladding, the Si3N4 ceramic matrix is prepared by conducting ball milling and mixing on Si3N4 powder, Y2O3 powder and MgO powder, then conducting ball milling and ball milling, and finally obtaining the multilayer titanium boride cladding Si3N4-based ceramic cutting tool, the multilayer titanium boride cladding Si3N4-based ceramic cutting tool, the multilayer titanium boride cladding Si3N4-based ceramic cutting tool and the multilayer titanium boride cladding Si3N4-based ceramic cutting tool. The obtained mixed powder A is subjected to hot pressed sintering under the protective atmosphere at the axial pressure of 30-40 MPa and the temperature of 1700-1850 DEG C, and the composite material is obtained. The multi-layer titanium boride cladding is prepared by the following steps: firstly, carrying out ball milling and mixing on titanium boride powder, Co powder and Mo powder, mixing the prepared mixed powder B and a PVA solution to obtain a coating, immersing a Si3N4 ceramic matrix into the coating, taking out and drying to obtain a blank, and carrying out pressureless sintering at 1700-1850 DEG C to obtain the multi-layer titanium boride cladding. The cutter has high hardness, high toughness and high wear resistance, and can be applied to the field of titanium alloy cutting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic cutting tools, and in particular, relates to a multi-layer titanium boride-clad Si3N4-based ceramic cutting tool and a preparation method and application thereof. Background Art

[0002] Titanium boride ceramics have extremely high hardness and wear resistance, good chemical stability, will not react with titanium alloy when cutting titanium alloy, and can also produce B2O3 liquefied film to play a self-lubricating role. However, titanium boride ceramics have low toughness and poor chipping resistance. They are prone to chipping during high-speed cutting of titanium alloys, resulting in tool failure. Although Si3N4 ceramics have lower hardness, their fracture toughness is much higher than that of titanium boride ceramics. They have high strength and good resistance to thermal shock and mechanical shock. Si3N4 ceramics are widely used in the field of ceramic tools. Si3N4 ceramic tools have more severe tool wear when cutting titanium alloys, but have higher chipping resistance, so it is necessary to improve their wear resistance when used as tools. Summary of the invention

[0003] In order to solve the above-mentioned shortcomings of the prior art, the present invention aims to provide a multi-layer titanium boride-clad Si3N4-based ceramic tool, which has better cutting performance than titanium boride tools.

[0004] Another object of the present invention is to provide a method for preparing the above-mentioned multi-layer titanium boride-clad Si3N4-based ceramic tool.

[0005] Another object of the present invention is to provide an application of the above-mentioned multi-layer titanium boride-clad Si3N4-based ceramic tool.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A multi-layer titanium boride clad Si3N4-based ceramic tool consists of a Si3N4 ceramic matrix and a multi-layer titanium boride clad. The Si3N4 ceramic matrix is ​​prepared by ball-milling Si3N4 powder, Y2O3 powder and MgO powder to obtain mixed powder A; applying 30-40MPa axial pressure to the mixed powder A under a protective atmosphere, and hot-pressing and sintering at 1700-1850°C. The multi-layer titanium boride clad is prepared by ball-milling titanium boride powder, Co powder and Mo powder to obtain mixed powder B, mixing the mixed powder B with a PVA solution to obtain a coating, immersing the Si3N4 ceramic matrix in the coating, taking out and drying to obtain a green body with a multi-layer titanium boride clad silicon nitride structure, and then pressurelessly sintering at 1700-1850°C.

[0008] Preferably, the particle sizes of the Si3N4 powder, Y2O3 powder, MgO powder, Co powder and Mo powder are all 0.1-2 μm, and the purity is all above 98%; the particle size of the titanium boride powder is 0.05-2 μm, and the purity is above 98%.

[0009] Preferably, the addition amount of Y2O3 powder in the Si3N4 ceramic matrix is ​​3-5wt.%; the addition amount of MgO powder is 3-5wt.%; the addition amount of Co powder in the multilayer titanium boride cladding is 1-3wt.%; and the addition amount of Mo powder is 3-5wt.%.

[0010] Preferably, the mass ratio of PVA to water in the PVA solution is (0.5-1):(9-9.5); the mass ratio of the mixed powder B to the PVA solution in the coating is (2-3):(7-8).

[0011] Preferably, the heating rate of the hot pressing sintering is 10-50°C / min, and the hot pressing sintering time is 30-180min; the heating rate of the pressureless sintering is 10-20°C / min, and the pressureless sintering time is 60-120min; the protective atmosphere is nitrogen or argon.

[0012] Preferably, the density of the Si3N4 ceramic matrix is ​​above 97%.

[0013] The method for preparing the multi-layer titanium boride-clad Si3N4-based ceramic tool comprises the following specific steps:

[0014] S1. Si3N4 powder, Y2O3 powder and MgO powder are added to ethanol and Si3N4 balls for ball milling and drying to obtain a mixed powder A; titanium boride powder, Co powder and Mo powder are added to ethanol and Si3N4 balls for ball milling and drying to obtain a mixed powder B;

[0015] S2. In a nitrogen atmosphere, the mixed powder A was loaded into a graphite mold, an axial pressure of 30 to 40 MPa was applied, the temperature was raised to 1700 to 1850 ° C at a rate of 10 to 50 ° C / min, and hot-pressed and sintered for 30 to 180 min to obtain a Si3N4 ceramic matrix;

[0016] S3. The mixed powder B was mixed with the PVA solution to obtain a coating, the Si3N4 ceramic substrate was immersed in the coating, removed and dried to obtain a multi-layer titanium boride-clad silicon nitride structure body;

[0017] S4. In a nitrogen atmosphere, the green body of the multi-layer titanium boride-clad silicon nitride structure is heated to 1700-1850°C at a rate of 10-20°C / min and pressurelessly sintered for 60-120 min to obtain a multi-layer titanium boride-clad Si3N4-based ceramic tool.

[0018] The application of the multi-layer titanium boride-clad Si3N4-based ceramic tool in the field of titanium alloy cutting.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The multi-layer titanium boride-clad silicon nitride structure tool of the present invention has high hardness, high toughness, high wear resistance, high strength, and good resistance to thermal shock and mechanical shock.

[0021] 2. The multi-layer titanium boride-clad silicon nitride structure tool of the present invention has better cutting performance than titanium boride tools and can be used in the field of titanium alloy cutting tools. DETAILED DESCRIPTION

[0022] The present invention is described in further detail below in conjunction with examples, but embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0023] Example 1

[0024] 1. Place a mixed powder of 92wt.% Si3N4 powder (particle size of 0.5μm, purity of 99wt.%), 4wt.% Y2O3 powder (particle size of 500nm, purity of 99wt.%) and 4wt.% MgO powder (particle size of 500nm, purity of 99wt.%) in a nylon ball mill, add ethanol and Si3N4 ball milling medium, the mass ratio of ball to material is 4:1, the ball milling time is 12h, the speed is 300r / min, and the ball mill is rotary evaporated and dried, and then passed through a 100-mesh sieve to obtain Si3N4-Y2O3-MgO mixed powder;

[0025] 2. Place a mixed powder of 96wt.% TiB2 powder (particle size of 0.5μm, purity of 99wt.%), 1wt.% Co powder (particle size of 500nm, purity of 99wt.%) and 3wt.% MgO powder (particle size of 500nm, purity of 99wt.%) in a nylon ball mill, add ethanol and Si3N4 ball milling media, the mass ratio of ball to material is 4:1, the ball milling time is 12h, the speed is 300r / min, and the ball mill is rotary evaporated and dried, and then passed through a 100-mesh sieve to obtain TiB2-Co-MgO mixed powder;

[0026] 3. The Si3N4-Y2O3-MgO mixed powder was loaded into a graphite mold, placed in a N2 atmosphere, applied with an axial pressure of 40 MPa, heated to 1800°C at a rate of 30°C / min, sintered by hot pressing and kept warm for 60 minutes to obtain Si3N4-based ceramics.

[0027] 4. The TiB2-Co-MgO mixed powder with a mass ratio of 1:4 was mixed with a PVA solution (PVA to water mass ratio of 1:9) to obtain a coating, and the Si3N4-based ceramic was immersed in the coating, and then taken out and dried for 10 minutes, and the cycle was repeated 5 times to obtain a green body with a multi-layer titanium boride-clad Si3N4 structure;

[0028] 5. In a nitrogen atmosphere, the green body of the multi-layer titanium boride-clad Si3N4 structure was heated to 1800°C at a rate of 10°C / min and pressurelessly sintered for 120 min to produce a multi-layer titanium boride-clad Si3N4-based ceramic tool with a cladding thickness of 4 to 5 μm.

[0029] The Si3N4-based ceramic has a density of 98.6%, a hardness of 18.5 GPa, and a fracture toughness of 6.8 MPa·m 1 / 2 ; The tool was used to cut titanium alloy, and the cutting parameters were: cutting speed V C =300m / min, back cutting depth ap=0.5, feed rate f=0.1, cutting mode is end face continuous cutting, tool life is 840m, and no obvious edge chipping occurs.

[0030] Example 2

[0031] 1. Place a mixed powder of 90wt.% Si3N4 powder (particle size of 0.5μm, purity of 99wt.%), 5wt.% Y2O3 powder (particle size of 500nm, purity of 99wt.%) and 5wt.% MgO powder (particle size of 500nm, purity of 99wt.%) in a nylon ball mill, add ethanol and Si3N4 ball milling medium, the mass ratio of ball to material is 4:1, the ball milling time is 12h, the speed is 300r / min, and the ball mill is rotary evaporated and dried, and then passed through a 100-mesh sieve to obtain Si3N4-Y2O3-MgO mixed powder;

[0032] 2. Place a mixed powder of 95wt.% TiB2 powder (particle size of 0.5μm, purity of 99wt.%), 2wt.% Co powder (particle size of 500nm, purity of 99wt.%) and 3wt.% MgO powder (particle size of 500nm, purity of 99wt.%) in a nylon ball mill, add ethanol and Si3N4 ball milling media, the ball-to-material mass ratio is 4:1, the ball milling time is 12h, the speed is 300r / min, and the ball mill is rotary evaporated and dried, and then passed through a 100-mesh sieve to obtain a TiB2-Co-MgO mixed powder;

[0033] 3. The Si3N4-Y2O3-MgO mixed powder was loaded into a graphite mold, placed in a N2 atmosphere, applied with an axial pressure of 40 MPa, heated to 1800°C at a rate of 30°C / min, sintered by hot pressing and kept warm for 60 minutes to obtain Si3N4-based ceramics.

[0034] 4. The TiB2-Co-MgO mixed powder with a mass ratio of 1:4 was mixed with a PVA solution (PVA to water mass ratio of 1:9) to obtain a coating, and the obtained Si3N4-based ceramic was immersed in the coating, and then taken out and dried for 10 minutes, and the cycle was repeated 5 times to obtain a green body with a multi-layer titanium boride-clad silicon nitride structure;

[0035] 5. In a nitrogen atmosphere, the green body of the multi-layer titanium boride-clad silicon nitride structure was heated to 1800°C at a rate of 10°C / min and pressurelessly sintered for 120 min to produce a multi-layer titanium boride-clad Si3N4-based ceramic tool with a cladding thickness of 4 to 5 μm.

[0036] The density of Si3N4-based ceramic in this embodiment is 98.9%, the hardness is 18.3 GPa, and the fracture toughness is 7.4 MPa·m 1 / 2 The tool was used to cut titanium alloy, and the cutting parameters were: cutting speed V C =300m / min, back cutting depth ap=0.5, feed rate f=0.1, cutting mode is end face continuous cutting, tool life is 756m, and no obvious edge chipping occurs.

[0037] Comparative Example 1

[0038] 1. Place a mixed powder of 92wt.% Si3N4 powder (particle size of 0.5μm, purity of 99wt.%), 4wt.% Y2O3 powder (particle size of 500nm, purity of 99wt.%) and 4wt.% MgO powder (particle size of 500nm, purity of 99wt.%) in a nylon ball mill, add ethanol and Si3N4 ball milling medium, the mass ratio of ball to material is 4:1, the ball milling time is 12h, the speed is 300r / min, and the ball mill is rotary evaporated and dried, and then passed through a 100-mesh sieve to obtain Si3N4-Y2O3-MgO mixed powder;

[0039] 2. The Si3N4-Y2O3-MgO mixed powder was loaded into a graphite mold, placed in a N2 atmosphere, applied with an axial pressure of 40 MPa, heated to 1800°C at a rate of 30°C / min, sintered by hot pressing and kept warm for 60 minutes to obtain Si3N4-based ceramics.

[0040] The density of Si3N4-based ceramic in this comparative example is 98.6%, the hardness is 18.6 GPa, and the fracture toughness is 6.8 MPa·m 1 / 2 The tool was used to cut titanium alloy, and the cutting parameters were: cutting speed V C =300m / min, back cutting depth ap=0.5, feed rate f=0.1, cutting mode is end face continuous cutting, tool life is 336m, and the main back tool face and tool tip are severely worn.

[0041] Comparative Example 2

[0042] 1. Place a mixed powder of 96wt.% TiB2 powder (particle size of 0.5μm, purity of 99wt.%), 1wt.% Co powder (particle size of 500nm, purity of 99wt.%) and 3wt.% MgO powder (particle size of 500nm, purity of 99wt.%) in a nylon ball mill, add ethanol and Si3N4 ball milling media, the mass ratio of ball to material is 4:1, the ball milling time is 12h, the speed is 300r / min, and the ball mill is rotary evaporated and dried, and then passed through a 100-mesh sieve to obtain a TiB2-Co-MgO mixed powder;

[0043] 2. The TiB2-Co-MgO mixed powder was loaded into a graphite mold, placed in a N2 atmosphere, applied with an axial pressure of 40 MPa, heated to 1800°C at a rate of 30°C / min, sintered by hot pressing and kept warm for 60 minutes to obtain TiB2-based ceramics.

[0044] The density of the TiB2-based ceramic in this comparative example is 98.1%, the hardness is 21.6 GPa, and the fracture toughness is 3.8 MPa·m 1 / 2 The tool was used to cut titanium alloy, and the cutting parameters were: cutting speed VC = 300m / min, back cutting depth ap = 0.5, feed rate f = 0.1, and cutting mode was end face continuous cutting. The tool life was 504m, and the tool had more severe chipping.

[0045] In summary, the multi-layer titanium boride-clad Si3N4-based ceramic tool of the present invention has excellent cutting performance, a tool life of more than 756 m, is more wear-resistant than the Si3N4-based ceramic tool of comparative example 1, and has stronger resistance to chipping than the TiB2-based ceramic tool of comparative example 2.

[0046] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A multi-layer titanium boride-clad Si3N4-based ceramic tool, characterized in that: The multi-layer titanium boride clad Si3N4-based ceramic tool is composed of a Si3N4 ceramic matrix and a multi-layer titanium boride clad. The Si3N4 ceramic matrix is ​​prepared by ball-milling Si3N4 powder, Y2O3 powder and MgO powder to obtain a mixed powder A; the mixed powder A is subjected to an axial pressure of 30 to 40 MPa under a protective atmosphere and hot-pressed sintered at 1700 to 1850° C.; the multi-layer titanium boride clad is prepared by first ball-milling titanium boride powder, Co powder and Mo powder to obtain a mixed powder B, mixing the mixed powder B with a PVA solution to obtain a coating, immersing the Si3N4 ceramic matrix in the coating, taking out and drying to obtain a green body with a multi-layer titanium boride clad silicon nitride structure, and then pressurelessly sintering at 1700 to 1850° C.

2. The multilayer titanium boride-clad Si3N4-based ceramic tool according to claim 1, characterized in that: The particle sizes of the Si3N4 powder, Y2O3 powder, MgO powder, Co powder and Mo powder are all 0.1-2 μm, and the purity is all above 98%; the particle size of the titanium boride powder is 0.05-2 μm, and the purity is above 98%.

3. The multi-layer titanium boride-clad Si3N4-based ceramic tool according to claim 1, characterized in that: The addition amount of Y2O3 powder in the Si3N4 ceramic matrix is ​​3-5wt.%; the addition amount of MgO powder is 3-5wt.%; the addition amount of Co powder in the multi-layer titanium boride cladding is 1-3wt.%; and the addition amount of Mo powder is 3-5wt.%.

4. The multi-layer titanium boride-clad Si3N4-based ceramic tool according to claim 1, characterized in that: The mass ratio of PVA to water in the PVA solution is (0.5-1):(9-9.5); the mass ratio of mixed powder B to PVA solution in the coating is (2-3):(7-8).

5. The multi-layer titanium boride-clad Si3N4-based ceramic tool according to claim 1, characterized in that: The heating rate of the hot pressing sintering is 10-50°C / min, and the time of the hot pressing sintering is 30-180min; the heating rate of the pressureless sintering is 10-20°C / min, and the time of the pressureless sintering is 60-120min; the protective atmosphere is nitrogen or argon.

6. The multi-layer titanium boride-clad Si3N4-based ceramic tool according to claim 1, characterized in that: The density of the Si3N4 ceramic matrix is ​​above 97%.

7. The method for preparing a multilayer titanium boride-clad Si3N4-based ceramic tool according to any one of claims 1 to 6, characterized in that: The specific steps include: S1. Si3N4 powder, Y2O3 powder and MgO powder are added to ethanol and Si3N4 balls for ball milling and drying to obtain a mixed powder A; titanium boride powder, Co powder and Mo powder are added to ethanol and Si3N4 balls for ball milling and drying to obtain a mixed powder B; S2. In a nitrogen atmosphere, the mixed powder A was loaded into a graphite mold, an axial pressure of 30 to 40 MPa was applied, the temperature was raised to 1700 to 1850 ° C at a rate of 10 to 50 ° C / min, and hot-pressed and sintered for 30 to 180 min to obtain a Si3N4 ceramic matrix; S3. The mixed powder B is mixed with the PVA solution to obtain a coating, the Si3N4 ceramic substrate is immersed in the coating, removed and dried to obtain a multi-layer titanium boride-clad silicon nitride structure body; S4. In a nitrogen atmosphere, the green body of the multi-layer titanium boride-clad silicon nitride structure is heated to 1700-1850°C at a rate of 10-20°C / min and pressurelessly sintered for 60-120 min to obtain a multi-layer titanium boride-clad Si3N4-based ceramic tool.

8. Application of the multi-layer titanium boride-clad Si3N4-based ceramic tool according to any one of claims 1 to 6 in the field of titanium alloy cutting.

Citation Information

Patent Citations

  • Silicon nitride ceramic cutter, and preparation method and application thereof

    CN112745127A